Nutrition Counseling and Education Skill Development, 4th Edition - Kathleen D. Bauer; Doreen Liou (Cengage Learning, 2020)
NUTRITION COUNSELING AND EDUCATION SKILL DEVELOPMENT helps entry-level nutritional professionals develop a solid foundation in counseling and education principles and evaluation methodologies. Taking a clear, engaging, step-by-step approach, the book includes case studies and first-person accounts and gives students opportunities in every chapter to practice new skills. Students learn to translate theoretical perspectives on nutrition counseling into effective dialogues that have the power to influence client knowledge, skills and attitudes. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.